Crafting courts in new democracies the politics of subnational judicial reform in Brazil and Mexico - Ingram, Matthew
"In Crafting Courts in New Democracies Matthew C. Ingram fills this gap by examining the varying strength of local judicial institutions in Brazil and Mexico since the 1980s. Combining statistical analysis and in-depth qualitative research, Ingram offers a rich account of the politics that shape subnational court reform in the region's two largest democracies. In contrast to previous studies, theoretical emphasis is given to the influence of political ideas over the traditional focus on objective, material incentives&quo